(untitled) (ENTHYMEMA, 2024)
The main thesis of this article is ‘no identity without boundaries’. It is therefore necessary to question identity, in the awareness that it is a polysemic notion: first of all, two modes of identity are distinguished, coincidence (the undivided subject) and non-coincidence with oneself (the divided subject). This distinction is essential for understanding the difference between ideology and theory: identity politics is merely an ideology of identity; and like any ideology it is schematic, dogmatic, and extremely poor. This is why it only deals with the simplest forms of subjectivity, which we can define by properties (woman, black, etc.) or by parts. One of the aims of this article is to show the philosophical backwardness, which is also political backwardness, of identity politics. The way to complexity is then indicated, first and foremost through psychoanalysis. However, Freud’s revolution (Group Psychology, 1921) was not understood by Lacan. The conception of a divided and flexible subject could be developed, on the one hand, by going beyond Lacanian scholasticism and, on the other hand, by exploring the strategic dimension, which continues to be ignored by theories of the event as well as those of the institution.